Hacia una agricultura sostenible, resiliente al clima y baja en emisiones. Región Andina - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Sustainable, climate-resilient and low-carbon agriculture is addressed, taking into account the current challenge for the agricultural sector in the Andean Region, it also identifies the actions carried out by the countries as a whole according to the sustainable development objectives, applying various strategies, from the adoption of conventional practices, to the incorporation of state-of-the-art technology; you are developed by the vision, vision of a sustainable agricultural sector in contribution to national priorities.